1984
DOI: 10.1002/ps.2780150612
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between three methods for determining the toxicity of chemicals to earthworms

Abstract: Three different laboratory methods for determining the toxicity of chemicals to earthworms were tested with a variety of pesticides and other chemicals. These methods, proposed by the EEC (Determination of Ecotoxicity of Chemicals), were: the Contact Filter Paper Test, in which the skin contact toxicity is tested by placing the organisms on treated filter paper; the Artificial Soil Test, in which the toxicity by skin and gut uptake is determined by adding the earthworms to an artificial soil made of sand, clay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…[33][34][35] For several earthworm species, the acute LC 50 values obtained by this test are poorly correlated with those from the 14-day artificial soil test. 36,37) The relatively decreased toxicity in the latter test was observed for pyrethroids and some other pesticides, 34,35) possibly due to lower bioavailability by tight adsorption to the substrate, faster degradation therein or more metabolic detoxification in the earthworm via dietary uptake. Metabolic transformation generally decreases a pesticide's toxicity, but the formation of more toxic metabolites should be noted, for example the oxon of an organophosphorus pesticide and the phenol of a phenoxy herbicide.…”
Section: Acute Toxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…[33][34][35] For several earthworm species, the acute LC 50 values obtained by this test are poorly correlated with those from the 14-day artificial soil test. 36,37) The relatively decreased toxicity in the latter test was observed for pyrethroids and some other pesticides, 34,35) possibly due to lower bioavailability by tight adsorption to the substrate, faster degradation therein or more metabolic detoxification in the earthworm via dietary uptake. Metabolic transformation generally decreases a pesticide's toxicity, but the formation of more toxic metabolites should be noted, for example the oxon of an organophosphorus pesticide and the phenol of a phenoxy herbicide.…”
Section: Acute Toxicitymentioning
confidence: 98%
“…61) Therefore, log K ow is a useful descriptor for analyzing the acute toxicity of pesticides. The 48-hr LC 50 values (µg/cm 2 ) from the paper contact tests using E. fetida for 86 pesticides and seven phenol derivatives [33][34][35][36][37]40) were first analyzed against log K ow (U.S. EPA EPI-Suite; http://www.epa.gov/opptintr/exposure/pubs/episuite. htm).…”
Section: Relationship With Pesticide Hydrophobicitymentioning
confidence: 99%
“…It is complicated to make a comparison between crab species because they have different etiology and habitants, however, because most crab species are detritivores, we consider them as a good option to do studies related to POPs exposure. There are several studies on earthworms with ecotoxicological background mainly focused on effects at population levels (lethality), at both laboratory controlled conditions (Heimbach, 1984;Ma & Bodt, 1993;Kula, 1995, Morrison et al, 2000 as in field ones (Thompson, 1970;Tomlin, 1981;Edwards & Brown, 1982;Haque & Ebing, 1983;Potter et al, 1994;Espinosa-Reyes et al, 2010), however, there are a few studies where exposure to POPs are evaluated, Jones and Hart (1998) revised works related to exposure of different earthworms species to various pesticides-Benomyl, Carbaryl, Carbendazim, Carbofuran, Chlordane, Methiocarb, Parathion, Pentachlorophenol, Phorate, Propoxur, Thiophanateme-. These same authors mentioned that earthworms of the Eisenia type are the most resistent to the pesticides previou s l y m e n t i o n e d .…”
Section: Resultsmentioning
confidence: 99%
“…Earthworms used in this study belonged to species commonly found in Egypt (Aporrectodea caliginosa). Individual worms were collected from dunghills around Alexandria Governorate and reared in artificial soil in large plastic containers (38 × 60 × 10 cm) covered with muslin cloth to reduce water evaporation, as described by Heimbach [24]. The worms were maintained in this artificial soil at 23 ± 2 ∘ C for one month before the experiments.…”
Section: Earthworms and Assaymentioning
confidence: 99%
“…Procedures used were based on those described by Heimbach [24]. Buprofezin and triflumuron were tested at 50, 100, 150, 200, and 300 mg active ingredient, a.i/kg artificial soil, while lufenuron was tested at 0.5, 1, 5, 10, and 25 mg/kg soil because it caused 100% mortality at concentration of 50 mg/kg soil.…”
Section: Toxicity and Growth-inhibitory Bioassay Against Earthworm Amentioning
confidence: 99%